Odpowiedź :
(2x-a)(2x+a)-(2x+a)^2=2 dla -1
4x²-a²-(4x²+4xa+a²)=2
4x²-a²-4x²-4xa-a²=2
-4xa-2a²=2
-2a²-4xa=2
-2a²-4*(-1)a=2
-2a²+4a=2
-2(a²-2a)=2
a²-2a=-1
a(a-2)=-1
a=-1
i a-2=-1
a=1
(x-a)(x+a)-(x-a)^2=8 dla 4
x²-a²-(x²-2xa+a²)=8
x²-a²-x²+2xa-a²=8
-2a²+2xa=8
-2(a²-xa)=8
a²-xa=-4
a²-4a=-4
a(a-4)=-4
a=-4 i a-4=-4
a=0
4x²-a²-(4x²+4xa+a²)=2
4x²-a²-4x²-4xa-a²=2
-4xa-2a²=2
-2a²-4xa=2
-2a²-4*(-1)a=2
-2a²+4a=2
-2(a²-2a)=2
a²-2a=-1
a(a-2)=-1
a=-1
i a-2=-1
a=1
(x-a)(x+a)-(x-a)^2=8 dla 4
x²-a²-(x²-2xa+a²)=8
x²-a²-x²+2xa-a²=8
-2a²+2xa=8
-2(a²-xa)=8
a²-xa=-4
a²-4a=-4
a(a-4)=-4
a=-4 i a-4=-4
a=0
(2x-a)(2x+a)-(2x+a)^2=2 dla -1
(2x+a)(2x-a-2x-a)=2
(2x+a)(-2a)=2
-4ax - 2a^2 -2 = 0 /:(-2) podstaw za x=-1
a^2 - 2a +1 = 0
(a-1)^2 = 0
a = 1
(x-a)(x+a)-(x-a)^2=8 dla 4
(x-a)(x+a-x+a) =8
(x-a) * 2a =8
2ax - 2a^2 = 8 /:2 podstaw za x=4
4a - a^2 - 4 = 0 /:(-1)
a^2 - 4a + 4 = 0
(a-2)^2 =0
a=2
(2x+a)(2x-a-2x-a)=2
(2x+a)(-2a)=2
-4ax - 2a^2 -2 = 0 /:(-2) podstaw za x=-1
a^2 - 2a +1 = 0
(a-1)^2 = 0
a = 1
(x-a)(x+a)-(x-a)^2=8 dla 4
(x-a)(x+a-x+a) =8
(x-a) * 2a =8
2ax - 2a^2 = 8 /:2 podstaw za x=4
4a - a^2 - 4 = 0 /:(-1)
a^2 - 4a + 4 = 0
(a-2)^2 =0
a=2